Sport tourism interrelationships, impacts and issues - Adair Daryl; Ritchie Brent W (New Delhi Viva Books, 2006)
This book examines the economic, social and environmental impacts and issues associated with the development of sport tourism globally, including the lack of research and coordination between industry and government. The book suggests the need for a more
Keywords: Sports; Tourism